Practice-based research on the teaching of mathematics: progress and imperatives for the future - Hoover, Mark; Ball, Deborah Loewenberg (NOMAD Nordic Studies in Mathematics Education, 2021)
Professional fields face persistent challenges in connecting practice and theory. In particular, tensions exist as to how theory and knowledge are developed, as well as what constitutes authority for practice. Together the articles in this issue explore three elements of the turn toward ”practice-based” research and professional education in mathematics education: designing teaching and learning in and for practice, learning mathematics teaching as a practice, and collaborating across professional roles and identities. In this commentary, we interrogate meanings of practice-based research on teaching and discuss themes across this collection of articles. We then argue for three imperatives for future efforts: (i) working on shared understandings of what the term ”practice-based” might mean; (ii) developing more nuanced conceptualizations of ”teaching”; and (iii) attending explicitly to justice in practice.